Quantitative computed tomography-based finite element analysis predictions of femoral strength and stiffness depend on computed tomography settings. Issue 1 (2nd January 2015) - Dragomir-Daescu, Dan; Salas, Christina; Uthamaraj, Susheil; Rossman, Timothy
Abstract The aim of the present study was to compare proximal femur strength and stiffness obtained experimentally with estimations from Finite Element Analysis (FEA) models derived from Quantitative Computed Tomography (QCT) scans acquired at two different scanner settings. QCT/FEA models could potentially aid in diagnosis and treatment of osteoporosis but several drawbacks still limit their predictive ability. One potential reason is that the models are still sensitive to scanner settings which could lead to changes in assigned material properties, thus limiting their results accuracy and clinical effectiveness. To find the mechanical properties we fracture tested 44 proximal femora in a sideways fall-on-the-hip configuration. Before testing, we CT scanned all femora twice, first at high resolution scanner settings, and second at low resolution scanner settings and built 88 QCT/FEA models of femoral strength and stiffness. The femoral set neck bone mineral density, as measured by DXA, uniformly covered the range from osteoporotic to normal. This study showed that the femoral strength and stiffness values predicted from high and low resolution scans were significantly different (p<0.0001). Strength estimated from high resolution QCT scans was larger for osteoporotic, but smaller for normal and osteopenic femora when compared to low resolution scans. In addition, stiffness estimated from high resolution scans was consistently larger than stiffness obtained from low resolution scans over the entire femoral dataset. While QCT/FEA techniques hold promise for use in clinical settings we provided evidence that further improvements are required to increase robustness in their predictive power under different scanner settings and modeling assumptions.